The billion dollar BET : - Pulley, Brett (John Wiley & Sons, 2004)
Praise for The Billion Dollar BET "In a gripping narrative that is both inspirational and cautionary, Brett Pulley tells us how Robert Johnson built Black Entertainment Television into a billion-dollar media empire. In a remarkable feat of reporting, without Johnson's cooperation, Pulley shows what it really takes to get ahead in America today, and in doing so provides as valuable a cultural as business history." --James B. Stewart Pulitzer Prize-winning journalist and bestselling author of DisneyWar, Den of Thieves, and Heart of a Soldier "Like or dislike? Agree or disagree? Bob Johnson's richly varied and fascinating life presses you against the window that Brett Pulley opens widely." --Bernard Shaw retired CNN anchor "Through his BET network, Bob Johnson reached the pinnacle of capitalism, the billionaire boys club, in the spirit of legions of driven, American moguls . . . Veteran business journalist Brett Pulley peels back the layers of this fascinating and complex entrepreneur." --Teri Agins Senior Special Writer, the Wall Street Journal, and author of The End of Fashion: How Marketing Changed the Clothing Business Forever